Enhancing Ethical Decision-Making in Public Administration Through Ethics Training and Organizational Culture - Anuang, Josep; Simantung, Leonardus; Albertus, Rafael (Journal Social Civilecial, 2023)
It is crucial in the area of public administration since the decision, in question, influences the public’s confidence, the administration, as well as the general welfare. This paper discusses ethics training with an intent of providing insights into the effectiveness of this measure in ethical decision making among public administrators, not ignoring the aspect of ethical education in raising awareness, and sharpening the skills of practical ethical decision making among the employees. Employing a purely qualitative approach, data were captured using purposively chosen participants who had undergone through ethics training programmes in their administrations. Analysis by themes indicated that ethics training helped the participants to reason ethically and identify solutions to ethical issues. Nevertheless, the research also found some barriers: resistance to change, regarding training in ethics as unnecessary, and lack of resources in enterprises. Equally as important, organizational culture was identified as a major factor influencing the success of the ethics training which proved that the organisational culture when supportive with leadership had a great contribution to the effectiveness of the training but when hierarchical bureaucratic it acted as a barrier. In this research, gaps concerning the context which shapes the effects and the practical application of ethics training in public administration are discussed. It also emphasise the relevance of integrating organisational practices by ethical principles and, therefore, the development of a socially responsible culture that may guarantee sustained ethical implementation and practices. The research results offer practical implications for policies to augment the ethics training programs within and across organizations.